Marketing of Livestock and Livestock Products in Sundarban Islands of India: a Participatory Rural Appraisal - Das, S. K.; Tripathi, H. (International Journal of Bio-resource and Stress Management, 2013)
Famous for the abode of man-eating Royal Bengal tiger Sundarban is a UNESCO world heritage site, biosphere reserve, largest delta and largest mangrove eco-system in the world. Agriculture and animal husbandry is the primary livelihood of people living in this region. Marketing is an important aspect of livestock production which has complementary and supplementary relationship with agriculture. Therefore, livestock and livestock products marketing in rural Sundarban is a virgin field of research. Since, interview and questionnaire-based research largely fail to capture the diversity and complexity of rural social reality case study method of PRA (Participatory Rural Appraisal) was used to understand livestock marketing system in four selected villages of Sundarban delta in India. Villages were selected based on backwardness, remoteness, and livelihood. Listing, topical interview, oral trend and ranking methods of PRA were employed to collect data. Data was verified through personal observation and key-informant discussion. Study reveals that a localized informal marketing system existed in the study area with a linkage to larger market of outside via the middleman (vendor). Further, it seems that marketing of livestock and its products was secondary to livestock production. Rules and regulations of marketing as well as the price of livestock and its products were standardized and determined informally based on local criteria and external market forces. Thus, the study provides useful insights into the marketing system of livestock and underlying social realities governing its functioning in Sundarban islands. It is concluded that similar kind of research conducted on a large scale will help development professionals and policy makers to plan and implement development programs in Sundarban where backwardness and rich natural resources paradoxically co-exist.